Interactions between genetic variants in the adiponectin, adiponectin receptor 1 and environmental factors on the risk of colorectal cancer. - Li Liu (PLoS ONE, 2011)
BACKGROUND: Metabolic syndrome traits play an important role in the development of colorectal cancer. Adipokines, key metabolic syndrome cellular mediators, when abnormal, may induce carcinogenesis. METHODOLOGY/PRINCIPAL FINDINGS: To investigate whether polymorphisms of important adipokines, adiponectin (ADIPOQ) and its receptors, either alone or in combination with environmental factors, are implicated in colorectal cancer, a two-stage case-control study was conducted. In the first stage, we evaluated 24 tag single nucleotide polymorphisms (tag SNPs) across ADIPOQ ligand and two ADIPOQ receptors (ADIPOR1 and ADIPOR2) among 470 cases and 458 controls. One SNP with promising association was then analyzed in stage 2 among 314 cases and 355 controls. In our study, ADIPOQ rs1063538 was consistently associated with increased colorectal cancer risk, with an odds ratio (OR) of 1.94 (95%CI: 1.48-2.54) for CC genotype compared with TT genotype. In two-factor gene-environment interaction analyses, rs1063538 presented significant interactions with smoking status, family history of cancer and alcohol use, with ORs of 4.52 (95%CI: 2.78-7.34), 3.18 (95%CI: 1.73-5.82) and 1.97 (95%CI: 1.27-3.04) for smokers, individuals with family history of cancer or drinkers with CC genotype compared with non-smokers, individuals without family history of cancer or non-drinkers with TT genotype, respectively. Multifactor gene-environment interactions analysis revealed significant interactions between ADIPOQ rs1063538, ADIPOR1 rs1539355, smoking status and BMI. Individuals carrying one, two and at least three risk factors presented 1.18-fold (95%CI:0.89-fold to 1.58-fold), 1.87-fold (95%CI: 1.38-fold to 2.54-fold) and 4.39-fold (95%CI: 2.75-fold to 7.01-fold) increased colorectal cancer risk compared with those who without risk factor, respectively (P(trend) <0.0001). CONCLUSIONS/SIGNIFICANCE: Our results suggest that variants in ADIPOQ may contribute to increased colorectal cancer risk in Chinese and this contribution may be modified by environmental factors, such as smoking status, family history of cancer and BMI.